META-ANALISIS: PROFIL TINGKAT KESIAPTERAPAN TEKNOLOGI HASIL PENELITIAN SOSHUM DI UNSOED TAHUN 2017-2019 - Nuniek Ina Ratnaningtyas; Dian Bhagawati; Sri Hartini; Saparso Saparso (Jurnal Ilmu dan Budaya, 2020)
The community service program (PPM) is the third Dharma college that must be implemented by all lecturers. The method used is generally in the form of technology transfer, either through training, education or hands-on practice. The technology applied must be a proven technology, no longer trial and error. The success of a university in carrying out PPM will be reflected in the performance achieved each year. The first year of research was focused on examining the research scheme managed by LPPM Unsoed with BLU funds for 2017-2019; the amount of funded research in the Soshum field and its suitability with TKT. The method used is a metaanalysis with a systematic review model, which is followed by FGD. The data and information obtained were analyzed thoroughly with an inductive approach based on the results of observations, interviews, discussions and secondary data to compile a descriptive abstraction with the stages of data reduction, data presentation and conclusion drawing. The results showed that there were 6 (six) research schemes that were always held by LPPM Unsoed in 2017-2019, namely: International Research Collaboration (IRC), Unsoed Leading Research, Unsoed Institutional Research, Competency Improvement Research, Beginner Lecturer Research and Special Task Facilities Professor. The number of Leading Research Development which was funded for the 2017-2019 period, in the Soshum field was 37 titles and Applied Leading Research which was funded for the 2018-2019 period, as many as 28 titles. Leading Research Development that has been carried out has conformity with TKT levels 7 and 8, while Applied Leading Research has conformity with TKT level 5 and level 6 with indicators for each Level of Technology Readiness (TKT) of Social Humainora and Education Types, according to Permenristekdikti 42/2016.